Influence of local and remote ischemic preconditioning on 3-min all-out exercise performance: a randomized controlled crossover study - Chidnok, W.; Kuo, Y.-H.; Chen, C.; Pan, C.-H.; Cheng, C.-F. (Journal of Exercise Science & Fitness, 2025)
Objective This study investigated the influences of local ischemic preconditioning (LIPC) and remote ischemic preconditioning (RIPC) on muscle deoxygenation before and during a 3-min all-out cycling test (3 MT), as well as on 3 MT performance.